Golgi-mediated vacuolar sorting of the endoplasmic reticulum chaperone BiP may play an active role in quality control within the secretory pathway - Pimpl, Peter; Hillmer, Stefan; Robinson, David G. (The plant cell, 2006)
Quality control in the endoplasmic reticulum (ER) prevents the arrival of incorrectly or incompletely folded proteins at their final destinations and targets permanently misfolded proteins for degradation. Such proteins have a high affinity for the ER chaperone BiP and are finally degraded via retrograde translocation from the ER lumen back to the cytosol. This ER-associated protein degradation (ERAD) is currently thought to constitute the main disposal route, but there is growing evidence for a vacuolar role in quality control. We show that BiP is transported to the vacuole in a wortmannin-sensitive manner in tobacco (Nicotiana tabacum) and that it could play an active role in this second disposal route. ER export of BiP occurs via COPII-dependent transport to the Golgi apparatus, where it competes with other HDEL receptor ligands. When HDEL-mediated retrieval from the Golgi fails, BiP is transported to the lytic vacuole via multivesicular bodies, which represent the plant prevacuolar compartment. We also demonstrate that a subset of BiP-ligand complexes is destined to the vacuole and differs from those likely to be disposed of via the ERAD pathway. Vacuolar disposal could act in addition to ERAD to maximize the efficiency of quality control in the secretory pathway.